2020
DOI: 10.1007/s11661-020-06039-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Post-processing in Additively Manufactured 316L Stainless Steels

Abstract: This paper provides a systematic examination of microstructure and corrosion behavior of additively manufactured 316L stainless steel after post-processing by surface finishing, isothermal heat treating, or hot isostatic pressing. The effects of isothermal heat treatments from 500°C to 1300°C and hot isostatic press processing from 1000°C to 1200°C were correlated to the evolution of microstructure, pore morphology and volume fraction, microhardness measurements, and corrosion behavior to reveal the different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Fonda et al investigated the mechanical and corrosion properties of heat treatment conditions in AM/316L SS material. Although the microstructure showed similar properties to this study, it was found that the corrosion properties in this study showed opposite properties to Fonda et al In this study, it was found that increasing heat treatment temperatures improved the corrosion properties of the material [62].…”
Section: Resultssupporting
confidence: 56%
“…Fonda et al investigated the mechanical and corrosion properties of heat treatment conditions in AM/316L SS material. Although the microstructure showed similar properties to this study, it was found that the corrosion properties in this study showed opposite properties to Fonda et al In this study, it was found that increasing heat treatment temperatures improved the corrosion properties of the material [62].…”
Section: Resultssupporting
confidence: 56%
“…The cells are columnar in nature with a size of the short axis in the range of 400–700 nm and the long axis has a length of several microns up to the full length of the primary austenite grain. It is important to note that regardless of their appearance as either equi-axed cells, ellipsoid cells or parallel lines (depending on the cutting angle with regards to the cell orientation), they are the same cells and not two different types of cells or dendrites, as has been reported [ 9 , 18 , 28 , 34 ]. As the misorientation is constrained to domain boundaries, the cell walls do not originate from bridging the misorientation between neighbouring cells.…”
Section: Discussionmentioning
confidence: 92%
“…The development of σ-phase after annealing at 800 °C for 5 h was confirmed by Kurzynowski et al [ 16 ]. High temperature annealing is generally observed to cause grain growth [ 10 , 17 ] and, eventually, recrystallization (or abnormal grain growth) and formation of equi-axed austenite grains at temperatures ≥1200 °C [ 18 ]. So far, only little research was dedicated to understanding the evolution of the amorphous silicates during heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, work presented by Reijonen et al shows the preservation of these cells at a HIP temperature of 1150 • C and a pressure of 100 MPa for four hours [36]. At shorter durations at increased temperatures, these cellular structures have been shown to be unaffected by heat treatment at 700 • C whilst becoming thinner and diffuse at 800 • C, with full removal observed at 900 • C [37][38][39][40]. The microstructure of treatment conditions 1 -HIP (T 700 P 100 ), 4 -HIP (T 700 P 137 ) and 7 -HIP (T 700 P 200 ), which refer to the low temperature treatment, are effectively identical to the as-built microstructure with the same key features being identifiable in representative images of low temperature treatment in Fig.…”
Section: Density and Microscopymentioning
confidence: 99%